1996
DOI: 10.1093/oxfordjournals.ndt.a027211
|View full text |Cite
|
Sign up to set email alerts
|

Uraemic pruritus and exposure to di(2-ethylhexyl)phthalate (DEHP) in haemodialysis patients

Abstract: Uraemic pruritus is a frequent and disabling symptom in patients on dialysis. The pathogenesis of uraemic pruritus is nevertheless still obscure. We investigated whether di(2-ethylhexyl)phthalate (DEHP), the most commonly used plasticizer in polyvinylchloride (PVC) haemodialysis tubings, is a possible pathogenetic factor in uraemic pruritus. Serum concentrations of DEHP and its major derivatives mono-(2-ethylhexyl)phthalate (MEHP), 2-ethylhexanol (2-EH) and phthalic acid (PA) were determined in uraemic patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 23 publications
0
28
0
2
Order By: Relevance
“…Neither patients nor healthy subjects reacted positively to patch tests [60]. Another study found that patients on HD are regularly exposed to considerable amounts of DEHP (plasticizer used in polyvinylchloride HD tubings), but no immediate relation to the occurrence or intensity of uremic pruritus was found [61].…”
Section: Cytokines and Possible Allergic Reactionsmentioning
confidence: 99%
“…Neither patients nor healthy subjects reacted positively to patch tests [60]. Another study found that patients on HD are regularly exposed to considerable amounts of DEHP (plasticizer used in polyvinylchloride HD tubings), but no immediate relation to the occurrence or intensity of uremic pruritus was found [61].…”
Section: Cytokines and Possible Allergic Reactionsmentioning
confidence: 99%
“…However, because phthalates are usual laboratory contaminants, human studies using the parent phthalates as biomarkers of exposure have been primarily limited to highly exposed populations (Ching et al 1981;Dirven et al 1993;Faouzi et al 1999;Mettang et al 1996;Pollack et al 1985). In 2000, we reported a novel approach, which uses phthalate monoester metabolites as biomarkers of exposure to phthalates (Blount et al 2000a).…”
Section: Measuring Human Exposure To Phthalatesmentioning
confidence: 99%
“…Heating of the stir bar released the extracted compounds into a GC-MS system for subsequent analysis in SIM mode. Analysis of MEHP in the infusates was done as their trimethylsilyl derivatives by GC-MS [21]. Briefly, mono(n-octyl)phthalate was used as internal standard and GC-MS analysis was performed in SIM mode.…”
Section: Quantification Of Dehp and Metabolites In Saline Infusatesmentioning
confidence: 99%